Comparison of Effects of Different Social Media Contents on Awareness - Kanya Majesta , Emmanuela; ., Daniel T. H. Aruan (KnE Social Sciences, 2020)
Businesses in today’s world are starting to use social media to convey marketing messages. There is an ongoing trend among businesses to use casual language and post light, humorous content in social media, in order to reach and connect with their consumers better. This research would examine the influence of different types of a brand’s social media content towards awareness. The objects of this research are social media profiles of two different brands. A total of 420 respondents are split into two equal groups. The first group is given a profile that applies a more informal content and the second group is given a more formal content. Data is processed using Structural Equation Modeling method. Results show that there is an important variable that precedes awareness, which is brand credibility. Besides, a significant effect towards awareness is shown in the group that receives formal social media content, but less on the group with informal content. The results of this study shows that shaping brand awareness through social media should be done through shaping the consumers’ perception that the brand is credible and trustworthy. Keywords: social media marketing, digital marketing, emotional brand attachment, awareness